2021
DOI: 10.1002/term.3174
|View full text |Cite
|
Sign up to set email alerts
|

Probing cell metabolism on insulin like growth factor(IGF)‐1/tumor necrosis factor(TNF)‐α and chargeable polymers co‐immobilized conjugates

Abstract: Cell culturing on different synthetic biomaterials would reprogram cell metabolism for adaption to their living conditions because such alterations in cell metabolism were necessary for cellular functions on them. Here we used metabolomics to uncover metabolic changes when liver cells were cultured on insulin‐like growth factor (IGF)/tumor necrosis factor‐α (TNF‐α) and chargeable polymers co‐modified biomaterials with the aim to explain their modulating effects on cell metabolism. The results showed that cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…3 ). Previous studies have also indicated that β-alanine may be associated with cell energy metabolism and proliferation ( Comerford et al, 2014 ; Li et al, 2018 ; You et al, 2021 ). The metabolic processing of tryptophan was notably increased in the MDCK-XF06 cell group.…”
Section: Discussionmentioning
confidence: 97%
“…3 ). Previous studies have also indicated that β-alanine may be associated with cell energy metabolism and proliferation ( Comerford et al, 2014 ; Li et al, 2018 ; You et al, 2021 ). The metabolic processing of tryptophan was notably increased in the MDCK-XF06 cell group.…”
Section: Discussionmentioning
confidence: 97%
“…A common feature of metabolism in the cancer cells is the ability to acquire necessary nutrients from a frequently nutrient‐poor environment and utilize these nutrients to both maintain viability and build new biomass 48 . Some studies have shown that Pantothenate and CoA biosynthesis signaling pathway was significantly altered in tumor cells 49–51 . DPD is a key enzyme in the Pantothenate and CoA biosynthesis signaling pathway (https://www.genome.jp/pathway/ko00770%2BK00207).…”
Section: Discussionmentioning
confidence: 99%